2002
DOI: 10.1002/pros.10166
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the enzymatic activity of prostate‐specific antigen by boric acid and 3‐nitrophenyl boronic acid

Abstract: PSA activity is inhibited in vitro by boric acid and NPBA. If degradation of fibronectin by PSA were, in fact, an important step in the progression of prostate cancer, then borate-induced inhibition of PSA activity should help reduce the development and proliferation of prostate carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 35 publications
0
42
0
1
Order By: Relevance
“…Specific interest in selenium as a chemopreventive agent for prostate cancer has arisen recently [41]. Lastly, PSA activity is inhibited in vitro by boron and boronated compounds [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific interest in selenium as a chemopreventive agent for prostate cancer has arisen recently [41]. Lastly, PSA activity is inhibited in vitro by boron and boronated compounds [26].…”
Section: Discussionmentioning
confidence: 99%
“…The blank was prepared containing the substrate in assay buffer. The details of the procedure are described elsewhere [18,26].…”
Section: Enzymatic Activity Of Psamentioning
confidence: 99%
“…Serine proteases are reversibly inhibited by simple and substituted boric acid compounds (Hunt and Idso, 1999). Barranco and Eckhert (2004) and Gallardo-Williams et al (2003) reported that boric acid inhibits human prostate cancer cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of nude mice, injected with androgen-sensitive LNCaP prostate cancer cells, with BA caused a reduction in tumour growth of 25 -38%, along with a reduction in plasma PSA levels of 88% (Gallardo-Williams et al, 2004). BA inhibits the activity of serine proteases, including prostate-specific antigen (PSA), presumably by binding to its active site (Bone et al, 1987;Gallardo-Williams et al, 2003). In culture, BA has been shown to inhibit the proliferation of LNCaP and the androgen-independent prostate cancer cell lines DU-145 and PC-3, in a dose-dependent manner (Barranco and Eckhert, 2004).…”
mentioning
confidence: 99%